Which staging system better predicts 10-year survival for gastric cancer? A study using an international multicenter database. Issue 8 (August 2018) - Lin, Jian-Xian; Lin, Jun-Peng; Li, Ping; Xie, Jian-Wei; Wang, Jia-Bin; Lu, Jun; Chen, Qi-Yue; Cao, Long-Long; Lin, Mi; Tu, Ru-Hong; Huang, Ze-Ning; Lin, Ju-li; et al.
Abstract: Purpose: Our aim was to evaluate the prognostic performance of the 8th edition AJCC staging system for gastric cancer survival after 10 years or more. Patients and methods: An international multicenter database was constructed (total n = 4537) by combining gastric cancer cases from the SEER database (n = 3066) and the database (n = 1471) of the Department of Gastric Surgery, Fujian Medical University Union Hospital. The relative discriminatory abilities were assessed using the likelihood ratio chi-square test, Akaike's Information Criterion (AIC) and Harrell's concordance index (c-statistic). Results: The 10-year overall survival rate for all the patients was 32.2%. A 2-step multivariate analysis showed that the 8th edition staging system was an independent factor for long-term overall survival. It also had higher likelihood ratio chi-square score, c-statistic and smaller AIC values compared with the 7th edition. However, stages IB and IIA of the TNM staging system showed a similar prognosis (both P > 0.05). Based on the survival data, we revised the 8th edition by merging stages IB and IIA into 1 category in the training set. The modified staging system demonstrated superior prognostic stratification with a higher c-statistic, likelihood ratio chi-square score and smaller AIC values compared to the 8th edition. Similar results were observed in the external validation set. Conclusion: The 8th edition AJCC TNM classification predicts the 10-year survival of gastric cancer patients more accurately than the 7th edition. However, by merging stages IB and IIA into 1 category, we propose a revised TNM stage system that provides an optimal prognosis.